High-throughput screening of microscale pitted substrate topographies for enhanced nonviral transfection efficiency in primary human fibroblasts - Adler, Andrew F. (2011)
Optimization of nonviral gene delivery typically focuses on the design of particulate carriers that are endowed with desirable membrane targeting, internalization, and endosomal escape properties. Topographical control of cell transfectability, however, remains a largely unexplored parameter. Emerging literature has highlighted the influence of cell-topography interactions on modulation of many cell phenotypes, including protein expression and cytoskeletal behaviors implicated in endocytosis. Using high-throughput screening of primary human dermal fibroblasts cultured on a combinatorial library of microscale topographies, we have demonstrated an improvement in nonviral transfection efficiency for cells cultured on dense micropit patterns compared to smooth substrates, as verified with flow cytometry. A 25% increase in GFP(+) cells was observed independent of proliferation rate, accompanied by SEM and confocal microscopy characterization to help explain the phenomenon qualitatively. This finding encourages researchers to investigate substrate topography as a new design consideration for the optimization of nonviral transfection systems.